The clinical toxicology of caffeine: A review and case study. (2018) - Willson, Cyril
Abstract: Caffeine is a widely recognized psychostimulant compound with a long history of consumption by humans. While it has received a significant amount of attention there is still much to be learned with respect to its toxicology in humans, especially in cases of overdose. A review of the history of consumption and the clinical toxicology of caffeine including clinical features, pharmacokinetics, toxicokinetics, a thorough examination of mechanism of action and management/treatment strategies are undertaken. While higher (i.e., several grams) quantities of caffeine are known to cause toxicity and potentially lethality, cases of mainly younger individuals who have experienced severe side effects and death despite consuming doses not otherwise known to cause such harm is troubling and deserves further study. An attempted case reconstruction is performed in an effort to shed light on this issue with a focus on the pharmacokinetics and pharmacodynamics of caffeine.